Surveillance, prevention, and control of vector-borne diseases 1 - Day, Jonathan (Henry Stewart Talks, 2021)
Vector-borne disease surveillance, Pathogen and disease detection, Spatial distribution of an outbreak, Temporal development of an outbreak, Transmission risk of a pathogen, Human Dengue 1934, Distribution of SLE virus, Surveillance techniques